Gait Recovery in Patients with Stroke with Severe Motor Damage: The Prognostic Role of Sensory Pathway Preservation. - Ju, Yeonwoo; Yoo, Yeun Jie; Yoon, Mi-Jeong; Hong, Bo Young; Lee, Jong In; Lim, Seong Hoon (NeuroRehabilitation, 2025)
Background: The role of sensory pathways in gait recovery remains unclear. We hypothesized that preservation of the somatosensory pathway may play a key role in gait recovery in patients with stroke and severe motor pathway impairment. Objective: This study aimed to investigate the impact of preserving the somatosensory pathway, spinothalamic tract (STT), and superior thalamic radiation (STR) on gait recovery in patients with chronic stroke and severe damage to motor pathways. Methods: This retrospective cross-sectional study included 85 patients and investigated the association between functional ambulation categories and the integrity of sensory pathways, as represented by fractional anisotropy values. Diffusion tensor imaging was performed to assess the integrity of the corticospinal tract (CST), cortico-ponto-cerebellar tract, STT, and STR 6 months after stroke. Results: Multivariable logistic regression analysis revealed that severe damage to the CST with the STT preserved yielded an odds ratio of 8.49 (p = 0.030) for functional gait, compared to when both tracts were damaged. Conclusions: Somatosensory pathways may play a critical role in gait recovery for patients with chronic stroke and severe motor tract damage. Preserving the somatosensory pathway could facilitate gait recovery in patients with severe motor pathway damage, offering valuable insights for future stroke rehabilitation strategies.